2009
DOI: 10.1016/j.jpsychires.2008.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of trauma-related distractors on neural systems for working memory and emotion processing in posttraumatic stress disorder

Abstract: The relevance of emotional stimuli to threat and survival confers a privileged role in their processing. In PTSD, the ability of trauma-related information to divert attention is especially pronounced. Information unrelated to the trauma may also be highly distracting when it shares perceptual features with trauma material. Our goal was to study how trauma-related environmental cues modulate * Corresponding author. Address: Department of Psychiatry and Behavioral Sciences, Duke University Medical Center, Box 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
171
2
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 182 publications
(194 citation statements)
references
References 40 publications
16
171
2
5
Order By: Relevance
“…While our study found CMA functional connectivity with dACC, this functional connection was not modulated by PTSD. The cortical targets of the BLA that we found were modulated by PTSD, including pregenual ACC/dorsomedial PFC and dACC, and are strongly implicated in PTSD by behavioral and cognitive challenge tasks (Milad et al, 2009;Morey et al, 2009). These cortical targets have myriad functions, but are also primary components of the default mode and salience networks.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While our study found CMA functional connectivity with dACC, this functional connection was not modulated by PTSD. The cortical targets of the BLA that we found were modulated by PTSD, including pregenual ACC/dorsomedial PFC and dACC, and are strongly implicated in PTSD by behavioral and cognitive challenge tasks (Milad et al, 2009;Morey et al, 2009). These cortical targets have myriad functions, but are also primary components of the default mode and salience networks.…”
Section: Discussionmentioning
confidence: 68%
“…The prefrontal and sensory-association cortical regions in these systems project primarily to the BLA (Hartley and Phelps, 2010), although recent research has also implicated the CMA in fear learning (LeDoux, 2012). Thus, our first hypothesis was that PTSD would be linked to altered BLA connectivity with key cortical regions such as ventromedial prefrontal cortex (PFC) (Myers and Davis, 2007), ACC (Gilboa et al, 2004), insula (Simmons et al, 2009), and inferior frontal gyrus (IFG) (Morey et al, 2009), and PTSD would be linked to altered CMA connectivity with regions underlying fear expression such as striatum, midbrain, and thalamus (LeDoux, 1998). Our second hypothesis, based on the role of BLA in fear conditioning, was that PTSD would modulate the divergent functional connectivity of BLA and CMA with its target regions.…”
Section: Introductionmentioning
confidence: 99%
“…First, prior studies suggest increased susceptibility to negative distraction during induced stress (Oei et al 2006(Oei et al , 2012 as well as in patients with stress-related disorders (e.g., PTSD, Morey et al 2009). Second, prior studies suggest that MT may reduce reactivity to negative images (Brefczynski-Lewis et al 2007;Ortner et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, delayed-recognition tasks, as described above, have been used to investigate the impact of laboratoryinduced stress (Oei et al 2006) as well as stress-related disorders (PTSD, Morey et al 2009) on component processes of WM. Oei et al (2006) reported that task performance during high-but not low-load trials was worse in individuals induced to experience psychosocial stress via the Trier stress test versus those in a no-stress group.…”
mentioning
confidence: 99%
See 1 more Smart Citation